Plant-Derived Monoterpene Therapies in Parkinson’s Disease Models: Systematic Review and Meta-Analysis - Matías Jávega-Cometto; Aracely J. Naranjo-Viteri; Leandro G. Champarini; Claudia B. Hereñú; Rosana Crespo (Plants)
Monoterpenes (MTs) are plants’ secondary metabolites and major components of essential oils (EOs), widely used in the pharmaceutical industry. However, its neuroprotective effects, particularly in Parkinson’s disease (PD) have not been fully demonstrated. PD is a progressive neurological disorder marked by dopaminergic neuron loss in the substantia nigra, motor symptoms being the most reported ones. This review evaluates the evidence supporting the use of MTs as potential neuroprotective agents. PubMed, SCOPUS, Google Scholar, and ScienceDirect databases were searched for articles on MTs in murine models with any type of administration. The PRISMA guidelines were followed. After screening 405 records, 32 were included in the systematic review and 30 were included in the meta-analysis. Fifteen MTs, commonly found in EOs, were identified as potential therapeutic agents for PD. The meta-analysis revealed that MTs administration improved motor performance, increased tyrosine hydroxylase levels, reduced oxidative stress markers (malondialdehyde) and proinflammatory cytokines (IL-6, IL-1, TNF-α), and enhanced antioxidant enzymes (catalase, superoxide dismutase) in parkinsonian animals. The antioxidant and anti-inflammatory properties of MTs appear to be key mechanisms in mitigating dopaminergic neurodegeneration. However, further clinical research is essential to translate these findings into practical applications.